Dental Informatics Integrating Technology into the Dental Environment - Abbey, Louis M.; Zimmerman, John L. (Health Informatics, 1992)
Dentistry today is changing because of new knowledge networks based on electronic technology. This book tells practitioners, administrators and educators what is happening in dentistry and how to use the full potential of new information technologies. Specifics such as existing machines, operating systems, software packages and user support groups are discussed. Aspects of standards for storage, access, and the use of information as well as its integration into the dental practice are covered. More general topics cover the impact of dental informatics on dentistry training programs, the dental manufacturing industries and insurance